Comparative genomics reveals insights into avian genome evolution and adaptation - Zhang, G.; Li, C.; Li, Q.; Li, B.; Larkin, D.; Lee, C.; Storz, J.; Antunes, A.; Greenwold, M.; Meredith, R.; Odeen, A.; Cui, J.; et al. (The American Association for the Advancement of Science, 2014)
Birds are the most species-rich class of tetrapod vertebrates and have wide relevance across many research fields. We explored bird macroevolution using full genomes from 48 avian species representing all major extant clades. The avian genome is principally characterized by its constrained size, which predominantly arose because of lineage-specific erosion of repetitive elements, large segmental deletions, and gene loss. Avian genomes furthermore show a remarkably high degree of evolutionary stasis at the levels of nucleotide sequence, gene synteny, and chromosomal structure. Despite this pattern of conservation, we detected many non-neutral evolutionary changes in protein-coding genes and noncoding regions. These analyses reveal that pan-avian genomic diversity covaries with adaptations to different lifestyles and convergent evolution of traits.